2009
DOI: 10.1161/hypertensionaha.109.138586
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin Receptor Blocker Prevented β-Amyloid-Induced Cognitive Impairment Associated With Recovery of Neurovascular Coupling

Abstract: Abstract-Recent studies suggest that vascular risk factors play a considerable role in the development of Alzheimer disease. Furthermore, the use of antihypertensive drugs has been suggested to reduce the incidence of dementia, including Alzheimer disease. In this study, we examined the effects of an angiotensin receptor blocker, olmesartan, on ␤-amyloid-induced cerebrovascular dysfunction and cognitive impairment. Oral administration of a low dose of olmesartan attenuated cerebrovascular dysfunction in young … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
83
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(86 citation statements)
references
References 31 publications
(18 reference statements)
3
83
0
Order By: Relevance
“…[16][17][18][19][20][21] In addition, as angiotensin-converting enzyme inhibitors, angiotensin receptor blockers and potassium sparing diuretics have an advantage in preventing CI, activation of the renin-angiotensin system or low potassium concentration has been suggested to be involved in CI through possible contributors to CI pathogenesis, including oxidative stress, inflammation, platelet aggregation and vasoconstriction. [22][23][24][25][26][27][28][29] Aldosterone, a crucial factor downstream of the renin-angiotensinaldosterone system, has also been shown to cause target organ damage independent of its effects on blood pressure and to be a potent cerebrovascular risk factor. In this study, we showed that increased PAC is associated with CI.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19][20][21] In addition, as angiotensin-converting enzyme inhibitors, angiotensin receptor blockers and potassium sparing diuretics have an advantage in preventing CI, activation of the renin-angiotensin system or low potassium concentration has been suggested to be involved in CI through possible contributors to CI pathogenesis, including oxidative stress, inflammation, platelet aggregation and vasoconstriction. [22][23][24][25][26][27][28][29] Aldosterone, a crucial factor downstream of the renin-angiotensinaldosterone system, has also been shown to cause target organ damage independent of its effects on blood pressure and to be a potent cerebrovascular risk factor. In this study, we showed that increased PAC is associated with CI.…”
Section: Discussionmentioning
confidence: 99%
“…Topical superfusion of soluble Ab 1À40 on the mouse neocortex yielded results that were in line with the in vitro findings. It led to an attenuation of resting CBF and of the CBF increase evoked by whisker stimulation or by endotheliumdependent vasodilators, as measured by laser Doppler flowmetry (LDF) (Niwa et al, 2000a, b;Deane et al, 2003;Park et al, 2005;Takeda et al, 2009). These effects were abolished by free radical scavengers or by substitution of methionine with norleucin at residue 35 of Ab 1À40 , a modification that prevents free radical generation by the peptide (Niwa et al, 2000b).…”
Section: Exogenous Ab Applicationmentioning
confidence: 99%
“…In addition, APP mice feature impaired autoregulatory ability, a homeostatic mechanism that ensures constant blood flow during changes in mean arterial pressure. Animals thus lack protection against ischemia (Niwa et al, 2002b;Takeda et al, 2009). The CBF increase to hypercapnia and endothelium-independent vasodilators such as SNAP (S-nitroso-N-acetylpenicillamine) or SNP (sodium nitroprusside) is either maintained (Iadecola et al, 1999;Niwa et al, 2000a;Christie et al, 2001;Shin et al, 2007) or impaired (Park et al, 2005;Han et al, 2008) in young Tg2576 mice, suggesting variable degree of smooth muscle dysfunction.…”
Section: Transgenic Mouse Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…n=5-6 rats. ** telmisartan suppressed the expression of the proteolytic enzyme β-secretase, which produces Aβ from the beta-amyloid precursor protein (APP) 34) ; suppression of cerebral blood flow lowering in AD model animals inhibited the hypometabolism of Aβ 13,35) ; and acceleration of APP ubiquitination renders it easily degradable.…”
Section: Discussionmentioning
confidence: 99%